2021
DOI: 10.1158/0008-5472.can-20-4245
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Imaging Identifies the VEGF–TXA2 Axis as a Critical Promoter of PGE2 Secretion from Tumor Cells and Immune Evasion

Abstract: Prostaglandin E2 (PGE2) promotes tumor progression through evasion of antitumor immunity. In stark contrast to cyclooxygenase-dependent production of PGE2, little is known whether PGE2 secretion is regulated within tumor tissues. Here, we show that VEGF-dependent release of thromboxane A2 (TXA2) triggers Ca2+ transients in tumor cells, culminating in PGE2 secretion and subsequent immune evasion in the early stages of tumorigenesis. Ca2+ transients caused cPLA2 activation and triggered the arachidonic acid casc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The ability of nanobodies to bind to the cell surface of the SARS-CoV-2 spike was studied by fluorescence-activated cell sorting (FACS) 87 . K562 cells expressing the SARS-CoV-2 spike were incubated with 1 μg ml –1 purified nanobody on ice for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of nanobodies to bind to the cell surface of the SARS-CoV-2 spike was studied by fluorescence-activated cell sorting (FACS) 87 . K562 cells expressing the SARS-CoV-2 spike were incubated with 1 μg ml –1 purified nanobody on ice for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The cytokine IL-4 plays an important role in regulating intestinal barrier function, is mainly synthesized by activated lymphocytes, and can inhibit the production of other cytokines, including IL-1, IL-6, IL-8 and TNF-α, and the generation of lymphocytes and macrophages[ 30 ]. Several studies have reported that in IBD, IL-4 significantly reduced vascular endothelial growth factor (VEGF) and inhibited the formation of blood vessels[ 31 ], but the expression of VEGF in the tumor tissues of patients with colorectal tumors was significantly increased[ 32 ]. The results of this study indicated that PRKCA was involved in the regulation of the proliferation, differentiation, survival, migration, cell polarity and cell cycle of various cancer cells; in mediating cell proliferation, differentiation, cell cycle progression and apoptosis; in regulating gene expression; and in promoting tumor formation and metastasis and participates in metabolic regulation[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high TXA 2 release from tumor cells likely co-opts this regulatory mechanism to modulate anti-tumor immunity directly. Moreover, TP stimulation of Ca 2+ transients by TP activation suppresses CD8+ T cells and cDC1 in Braf V600E melanoma and 4T1 Breast cancer allografts [ 124 ]. This modulation of acquired immunity promotes immune evasion in the early stages of tumorigenesis and identifies TP signaling as an essential immunomodulator of the tumor microenvironment.…”
Section: Immune Modulation By Txa 2 Signaling In C...mentioning
confidence: 99%